GE_GERICHTE C/19581/2014 vom 7. September 2015 - GE Cour de justice (2015)
DIVORCE; AUTORITÉ PARENTALE; RELATIONS PERSONNELLES; OBLIGATION D'ENTRETIEN | CC.273.1; CC.285.1; CC.298.1; CC.308.2; RAVS.52f bis